Leaf Epidermal Anatomy of Euphorbiaceae and Phyllanthaceae from the Kaliurang Sector of Mount Merapi, Indonesia - Riska Annisa; Dewi Sartika Amboupe; Muliana GH; Jamilatus Sa'diyah; Syaidah Fitri; Naufal Hafidh Mahdi Sujarwo Putra; Wendy A. Mustaqim (Jurnal Biologi Tropis, 2026)
Euphorbiaceae and Phyllanthaceae are diverse seed plant families whose classification has been extensively studied, particularly since molecular evidence established Phyllanthaceae as a distinct family. This study investigated leaf epidermal anatomy of species occurring in Central Java, Indonesia, to provide additional evidence for their taxonomic characterization. Twelve species representing six genera were examined, comprising five Euphorbiaceae and seven Phyllanthaceae species, including ten native and two introduced species. Leaf epidermal sections were analyzed based on epidermal cell shape, anticlinal wall patterns, stomatal types, and stomatal distribution. Anomocytic stomata were observed only in Euphorbia heterophylla and Euphorbia hirta, suggesting their potential as diagnostic characters. Amphistomatic leaves occurred in E. heterophylla and Phyllanthus niruri, whereas the remaining species were hypostomatic. However, diacytic stomata, epidermal cell shapes, and anticlinal wall patterns overlapped between the two families. Non-metric multidimensional scaling (NMDS) analysis also failed to clearly separate the species according to family classification. These findings indicate that leaf epidermal characters are useful for species-level characterization but do not consistently distinguish Euphorbiaceae from Phyllanthaceae. The study provides baseline anatomical data for tropical Indonesian species and highlights the need for further research incorporating broader anatomical and morphological characters.